Impact of spectacle use on academic performance among Vietnamese adolescents with reduced visual acuity and myopia: A school-based study. - Hoang Thuy Linh Nguyen; Xuan Minh Tri Tran; Keiko Nakamura; Kaoruko Seino; Yuri Tashiro; Ayano Miyashita; Tae Igarashi-Yokoi; Van Thang Vo; Kyoko Ohno-Matsui (PLoS ONE)
Objectives Untreated cataracts and uncorrected refractive errors are the leading causes of vision impairment worldwide. Timely correction of refractive errors can significantly improve visual function and daily life. This study examined the impact of spectacle use on the academic performance of schoolchildren with reduced visual acuity (VA) and myopia. Methods This cross-sectional study included 647 students from five secondary schools in Hue City, Vietnam. Students underwent comprehensive eye examinations, including VA, autorefractometry, and axial length measurements, and a structured questionnaire was completed. The primary outcome was academic performance, based on grade point average (GPA), math, and literature scores. Generalized linear models were utilized to examine the association between spectacle use and students' academic performance. Results The mean spherical equivalent was -0.92 ± 1.62 diopters, and the mean axial length was 23.32 ± 1.07 mm. The prevalence of reduced VA (uncorrected VA ≤ 7/10) and myopia (spherical equivalent ≤ -0.5 diopters) was 23.2% and 48.7%, respectively. Almost two-thirds of myopic students did not wear spectacles. Spectacle use was found to be significantly associated with an increased GPA (β = 0.462; 95% confidence interval = 0.108-0.816), math scores (β = 0.517; 95% confidence interval = 0.015-1.020), and literature scores (β = 0.438; 95% confidence interval = 0.074-0.802) among students with reduced VA, and with increased literature scores (β = 0.277; 95% confidence interval = 0.046-0.509) among students with myopia. Conclusions Refractive errors, particularly myopia, are major health concerns among secondary school students in Vietnam. Despite the need for corrective spectacles, many students do not wear them, exacerbating their vision problems. This study highlights the benefits of spectacles in improving academic performance for students with reduced VA and myopia.